2019
DOI: 10.4103/sjamf.sjamf_66_18
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of spontaneous intracerebral hemorrhage

Abstract: Background Spontaneous, nontraumatic intracerebral hemorrhage (ICH) remains a significant cause of morbidity and mortality throughout the world. Although ICH has traditionally lagged behind ischemic stroke and aneurysmal subarachnoid hemorrhage in terms of evidence from clinical trials to guide management, the past decade has seen a dramatic increase in studies of ICH intervention. Aimof study The aim of the study is to assess the benefits of surgical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…It has been reported that SICH is most commonly located in the basal ganglia (50%-60%) 16. Consistent with this study, hematomas were most commonly localized in the deep region in our study (37 patients [69.8%]).…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that SICH is most commonly located in the basal ganglia (50%-60%) 16. Consistent with this study, hematomas were most commonly localized in the deep region in our study (37 patients [69.8%]).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to Alkhadrawy et al, (10) study, he concluded that The basal ganglia is the most common site of ICH, representing 50-60% of spontaneous ICH, and basal ganglia ICH is associated with 50% mortality rate. In our study ICH occurred in basal ganglia in 55%.…”
Section: Discussionmentioning
confidence: 72%
“…The best candidates for ICH evacuation are those with hematoma volume 30-60 ml and GCS more than 10. [10] While patients with poor GCS at presentation and pupillary inequality suggests greater primary brain injury and herniation leading to prolonged ventilator support. Most of these patients end up in vegetative state.…”
Section: Outcome Of Surgical Evacuation Of Spontaneous Supratentorial...mentioning
confidence: 99%